Grafting-Induced Phenotypic and Genomic Variations in Cassava (Manihot esculenta Crantz) through Interspecific Compatibility with M. Glaziovi - Ulfa, Umi Tahniah; Sudarsono, Sudarsono; Ardie, Sintho Wahyuning; Mulyaningsih, Enung Sri; Hartati, N. Sri; Anjarsari, Nurul Aeni; Dewi, Prita Sari (Department of Agronomy and Horticulture, IPB University, 2025)
Grafting is a promising approach to enhance cassava (Manihot esculenta Crantz) productivity, particularly in improving tuber yield and quality. Despite its technical simplicity, research on the morphological and molecular consequences of grafting in cassava is limited. This study aimed to quantitatively assess phenotypic differences between grafted and shoot cutting plants and characterize genetic modifications in shoot apical meristems near the graft union. Three splice-grafting combinations were evaluated: M. glaziovii (cv.